ChemInform Abstract: One‐Pot Two‐Step Microwave‐Assisted Synthesis of Alkylidene Acetoacetamido Esters, Useful Intermediates for β‐Dehydropeptides. Issue 46 (October 2016) - Viola, Angelo; Ferrazzano, Lucia; Greco, Roberto; Cerisoli, Lucia; Caldi, Jonathan; Tolomelli, Alessandra
Abstract: A one‐pot two‐step protocol for the preparation of amino‐acid‐derived unsaturated acetoacetamides is optimized.